Alan Shearer my story so far - Shearer, Alan (Coronet, 1998)
Alan Shearer has been the English player of his generation. This work charts various aspects of his rise to fame, exploring his unique relationships with Kenny Dalglish and Kevin Keegan, his position as captain of his country's team, and his international career, working with Graham Taylor, Terry Venables, Glenn Hoddle and Ruud Gullit.